Outcomes of True Zero-Fluoroscopy Catheter Ablation for Atrial Fibrillation Care: A Systematic Review and Meta-analysis - Nathania Ella Sudiono; Christopher Daniel Tristan; Muhammad Farid Hamka; Erlangga Masykur Kynaya; Awalil Rifqi Kurnia Rahman; Irnizarifka Irnizarifka (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2026)
Introduction: Atrial fibrillation (AF) represents the most common arrhythmia. Current guidelines recommending catheter ablation as first-line rythm control and definitive treatment for AF which resistant or unresponsive to antiarrhythmic drugs. However, there is concerning issue of fluoroscopy radiation regarding conventional catheter ablation. Zero-fluoroscopy (ZF) emerged as novel technique to fully eliminated fluoroscopy with uncertainity of efficacy and safety. Previous review was insufficient, as they grouped fluoroless ablation under the ZF category. Method: Scopus, Pubmed, ScienceDirect, and CENTRAL were used to identify relevant studies prior to December 21, 2024. Studies directly comparing TZF vs NZF were included. Quality assessment was carried out using the RoB 2.0 and ROBINS-I tool. Meta-analysis was conducted using R-Studio. Discussion: There were one randomized controlled trial (RCT) and seven non-randomized cohorts (1.171 patients) included. The success of pulmonary vein isolation (PVI) with TZF and NZF was comparable, with follow-up visits showing equivalent AF recurrence rates at 6 months (RR = 1.00; 95% CI = 0.90 - 1.11; p = 0.99) and 12 months (RR = 0.57; 95% CI = 0.13 – 2.57; p = 0.47). ZF showed a significantly shorter procedural time duration (MD = -8.94; 95% CI = -13.56 – (-4.32); p < 0.01). Safety evaluation of ZF demonstrated comparable results for cardiac tamponade (RR = 1.77; 95% CI = 0.37 – 8.37; p = 0.47) and other adverse events risk. Conclusion: TZF technique in catheter ablation for AF is a revolutionary, effective, and safe innovation. TZF should be considered the standard approach in AF catheter ablation.